Development of p-resonant voltage control for dc motor using arduino - Abdullah, Abdul Hadi (2014)
This project described about to design and to development of P-Resonant voltage control for DC motor. The objective of P-Resonant controllers is applied to control the output voltage of the DC motor. An Arduino board device is used as a medium for the implementation of the control system design. The P-Resonant controller is developed and simulates using MATLAB/Simulink software. MATLAB block diagram is downloaded into Arduino which will generate the PWM signal. The signal is transmitted from the gate driver to the three phase rectifier to produce a direct current voltage for the motor. The voltage produced is in accordance with the specified value at the reference voltage. The actual voltage will try to reference voltage with the comparison method and control of the ' P-Resonant '. The difference is then corrected to minimize the voltage error. A simple hardware implementation of the PR voltage controller is designed and the experimental results are presented to demonstrate the validity of this approach. The results are observed in two main part; simulation and hardware. Each part has an open loop control and close loop control. It has been observed that the designed system has been successfully implemented.